IDENTIFIKASI TELUR CACING NEMATODA USUS PADA KUKU TANGAN PENGRAJIN GENTENG DI DESA PEJATEN, KEDIRI, TABANAN Ni Luh Gede Mulan Tirtayanti1, Cok. Dewi Widhya H.S.2, IGA. Sri Dhyanaputri3. - cok dewi (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2016)
Abstract Backgrounds: Workers have a risk of getting a disease caused by their job. Groups of workers while do their jobs are always in direct contact with soil as a medium of transmission of the worm eggs like roof tile maker. Based on data from health worm infection at Puskesmas I Kediri in the last three years there are three persons from Pejaten village who check worm infection and two of them showed positive result that they were infected by intestinal worm eggs. Objective: This study aims to find out the existence of the worm eggs Intestinal Nematode on the roof tile maker’s fingernails in Pejaten village, Kediri, Tabanan. Methods: This research did on January until June 2016. This research use descriptive study. Sample are taken with purposive sampling technique and researcher take 26 samples. The examination is searching for worm eggs at 26 fingernails specimens had done by floating methods using a solution of 2% eosin. Results: From this results, as much as 50% samples contained worm eggs. The infection rate of each worm eggs type is Ascaris lumbricoides 53,8%, Hookworm 23,1%, mix of Ascaris lumbricoides and Hookworm 15,4% and 7,7% of the sample identified containing worm eggs from the mix of Ascaris lumbricoides and Trichuris trichiura. Based on the characteristics of the respondents, high presence of worm eggs found in the range age 26-45 years 34,6%, male gender 30,8% and respondents who don’t attend school 23,1%. Based on the personal hygiene, high presence of worm eggs found in respondents who have bad habits of cutting nails 46,2%, bad handwashing habits 42,3%, respondents who don’t use hand gloves 50% and bad footwear usage habits 34,6%. Recommended: Suggestion for a roof tile maker are to maintain the cleanliness of nails, washing hands after contact with soil, and also using hand gloves and footwear while they working. Keyword : roof tile maker; fingernails; worm eggs.